(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
^^ dkO;s’kq ukVdae jE;e ^^ dg djlaLd`rkpk;ksZa us vkSj ^^ ukVd thou dh vuqd`fr gS^^ ¼Mªkek bZt bfeV’ku vkWQykbQ½ dgdj vkaXl lehkdksa us bl n`’;kRed lkfgR;d fo/kk vkSj thou ds laca/k dh?kfu"Brk dks n`